Comparative analysis of endoscopic submucosal dissection and surgical resection for early colorectal cancer - A. N. Sidorova; V. N. Klimenko; O. B. Tkachenko; M. V. Grinkevich; Yu. V. Petrik; O. V. Iaikova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was a comparative assessment of the efficacy and safety of surgical resection and endoscopic submucosal dissection in the treatment of early colorectal cancer.MATERIALS AND METHODS. We retrospectively evaluated 165 patients after endoscopic submucosal dissection (main group) and 70 patients after surgical resection (control group) with Tis-T1N0M0 stage of colorectal cancer. Median age was 65 and 67. According to the histological structure, the groups consisted mainly of differentiated types of adenocarcinoma.RESULTS. In the endoscopic group, all tumors were removed in a single block. Radical removal was recognized in 80.7% of cases. No progression was detected during the follow-up period. In the group of surgical resections,  progression was detected in 1 patient Postoperative complications in the endoscopic group were 9%, in the surgical group – 35.7%, class 3a and higher according to clavien–Dindo, 4.2 and 25.7%, respectively. When the tumor was localized in the rectum and rectosigmoid bend, there were significantly fewer complications in the main group than in the comparison group (4.2% vs. 20%). In the surgical group, a coloor ileostomy was formed temporarily in 28.6 % of cases, and in 10 % – for perpetuity. There were no treatment-related deaths in both groups.CONCLUSION. In this study, endoscopic submucosal dissection showed a technical success in 100% of cases, with a risk of major postoperative complications of 4.2% and radicality in 80.7% of cases. Standard surgical techniques, along with high oncological efficiency, show significant rate of major complications (25.7 %) and in 38.6 % of cases led to a temporary or permanent life-quality recession. Thus, endoscopic submucosal dissection, in the absence of a negative prognosis factors, is the method of choice in the radical treatment of colon cancer Tis-T1N0M0 due to its effectiveness and safety.